The p53 gene in patients under the age of 40 with gastric cancer: mutation rates are low but are associated with a cardiac location. Issue 4 (1st August 2000) - Rugge, M; Shiao, Y-H; Busatto, G; Cassaro, M; Strobbe, C; Russo, V M; Leo, G; Parenti, A R; Scapinello, A; Arslan, P; Egarter-Vigl, E
Abstract : Background —Determining both the frequency and the spectrum of p53 gene mutation in young patients with gastric cancer might provide clues to the host related genetic mechanism(s) in gastric carcinogenesis. Patients and methods —p53 mutations were assessed (by means of polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP), followed by DNA sequencing) in a cohort of 105 consecutive Italian patients in whom gastric cancer was ascertained before the age of 41. Results —A low prevalence of p53 mutations (eight of 105) was observed, with no significant difference between intestinal (three of 31; 10%) and diffuse (five of 74; 7%) phenotypes. A significantly higher prevalence of p53 mutations was associated with the cardiac location (odds ratio, 7.09; confidence interval, 1.56 to 32.11). In all but one case, p53 mutations were associated with a stage higher than I. All eight mutations were located at CpG sites, where G : C to A : T transitions have been associated with frequent methylation at the C5 position of cytosine. Conclusions —These findings show that, unlike what has been consistently demonstrated in the general population, p53 mutations are uncommon in gastric cancer occurring in young patients, and in such patients, p53 alterations are significantly associated with the cardiac location.